Magnetohydrodynamic cross-field boundary layer flow - D. B. Ingham; L. T. Hildyard (International Journal of Mathematics and Mathematical Sciences, 1982)
The Blasius boundary layer on a flat plate in the presence of a constant ambient magnetic field is examined. A numerical integration of the MHD boundary layer equations from the leading edge is presented showing how the asymptotic solution described by Sears is approached.